Reverse Logistics under omni-channel retailing - Kumar, Vidit (2019)
The evolution of omni-channel retailing has transformed the way retailers are selling their merchandise or products in the market. The advent of digitalization and consumer preferences has led to the evolution of omni-channel retailing. In omni-channel context the consumers are at the centre of every process or decision made by the retailer. Therefore, exploring the context of returns management or reverse logistics in the omni-channel retailing is the purpose of the study. The study identifies three main themes reverse logistics, management processes and return policy to analyze the process of product returns in the omni-channel environment. The research is completely a qualitative analysis. Additionally, the research paper focuses on the literature review about the topic and based on it develops the findings. The research paper attempts on providing rational discussions in relation to the findings and also suggests future studies.